Difference Operators
We have already seen one difference operator called divided
difference operator in the earlier section. We define few more difference
operators and their properties in this section.
Forward difference operator
:
Suppose that a fucntion f(x) is given at equally spaced discrete
points say x0, x1, . . . xn as
f0,
f1, . . . fn respectively. Also let
the constant difference between two consecutive points of x is called
the interval of differencing or the step length denoted by h. Then
the forward difference operator D is
defined as
Df(x) = f(x + h) - f(x) orDfi
= fi+1 - fi
where any typical fi = f(xi).
Similarly the higher differences are defined as
D2f(x)
= D(Df(x))
= D(f(x + h) - f(x))
= f(x + 2h) - 2f(x + h) + f(x)
= fi+2 - 2fi+1 + fi
or in general,
Dn f(x) = Dn-1(Df(x))
= Dn-1f(x + h) - Dn-1f(x)
Example :
Let a function f(x) is given at the points (0, 7), (4, 43),
(8,367) then find the forward difference of the function at x = 4.
Df(x) = f(x + h) - f(x)
ÞDf(4) = f(4 + h) - f(4)
= f(8) - f(4) = 367 - 43 = 324
Example :
Find Df(x) for the function
x2
+ 2x + 3 with h = 2
Df(x) = f(x + h) - f(x)
= (x + 2)2 + 2(x + 2) + 3 - x2
- 2x - 3
= x2 + 4x + 4 + 2x
+ 4 + 3 - x2
- 2x - 3
= 4x + 8
D2f(x) = 4(x
+ 2) + 8 - 4x - 8 = 4x + 8 - 4x = 8
D3f(x) = 8 -
8 = 0
Properties :
-
D(f(x) + g(x))
= Df(x) + Dg(x)
-
D(c f(x))
= c.Df(x) where c is a constant
-
If f(x) is a polynomial of degree n,
|
n
|
|
|
f(x) = |
S
|
ai xi |
then Dnf(x) is constant,
and is equal to ann!hn |
|
i=0 |
|
|
Proof :
Lets prove this by mathematical induction
for n = 1, f(x) = a0 + a1x
Df(x) = a0 + a1(x
+ h) - a0 - a1x = a1h
= a11!h1
assume that the formula is true for all polynomials upto the degree
n-1.
Consider the nth degree polynomial
|
|
( |
n
|
|
) |
Dn f(x) = |
Dn |
S
|
ai xi |
|
|
i=0
|
|
|
|
( |
n-1
|
|
) |
+ Dn(anxn) |
Dn f(x) = |
Dn |
S
|
ai xi |
|
|
i=0
|
|
=
0
+ an Dn xn
= 0 + an Dn-1((x +
h)n - xn)
= 0 + an Dn-1( nhxn-1
-
g(x))
where g(x) is a polynomial of degree less than (n-1) and hence
Dn-1g(x)
= 0
ÞDn f(x) = an Dn-1(
nhxn-1)
= an(nh)(n-1)!hn-1
= ann!hn.
Backward difference operator
: Ñ
The difference operator Ñ defined
by
Ñf(x) = f(x) - f(x-h)
Ñfi = fi
- fi-1
is called backward difference operator.
Ñ2fi
= Ñ(Ñfi)
= Ñ(fi - fi-1)
= fi - 2fi-1 + fi-2 and so on.
Central difference operator
:
d
The difference operator d
defined by
df(x) = f(x + h/2) - f(x - h/2)
dfi = fi + 1/2
- fi - 1/2
is called the central difference operator.
d2fi =
d(fi
+ 1/2 -
fi - 1/2) = (fi+1
- fi) -
(fi - fi-1)
= fi+1
- 2fi + fi-1
Shift operator :
Efi = fi+1, E2fi
= fi+2
Averaging operator :
mfi = 1/2 * (fi +
1/2 + fi - 1/2)
Some relations between various
operators :
-
E = 1 + D
Efi = fi+1 = fi+1 - fi
+ fi = (1 + D)fi
Þ E = 1 + D
|
¥ |
|
|
|
|
Enfi = |
S |
( |
n
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
for n = 1, E1fi = fi+1
= (1 + D)fi
|
¥ |
|
|
|
|
|
RHS is |
S |
( |
1
i
|
) |
Di fi |
= D0 fi+D1
fi
=
(1+D)fi |
|
k=0 |
|
|
|
|
|
Hence the result is true for n = 1, Assume now that the result
is true for the value (n-1) then
|
¥ |
|
|
|
|
En-1fi = |
S |
( |
n-1
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
consider
Enfi = E En-1fi
|
¥ |
|
|
|
|
= (1 + D) |
S |
( |
n-1
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
|
¥ |
|
|
|
|
= |
S |
( |
n-1
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
|
+ |
¥ |
|
|
|
|
S |
( |
n-1
i
|
) |
Di+1 fi |
k=0 |
|
|
|
|
|
|
¥ |
|
|
|
|
= |
S |
( |
n-1
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
|
+ |
¥ |
|
|
|
|
S |
( |
n-1
j-1
|
) |
Dj fi |
j=1 |
|
|
|
|
|
|
¥ |
|
|
|
|
|
|
|
|
|
|
|
|
= |
S |
[ |
( |
n-1
i
|
) |
+ |
( |
n-1
i
|
) |
] |
Di fi |
|
|
|
k=0 |
|
|
|
|
|
|
|
|
|
|
|
|
... |
( |
n-1
i
|
) = 0 |
and j is arbitrary |
|
¥ |
|
|
|
|
ÞEnfi = |
S |
( |
n
i
|
) |
Di fi |
|
k=0 |
|
|
|
|
|